2018
DOI: 10.1177/1350650118779495
|View full text |Cite
|
Sign up to set email alerts
|

Influence of granularity of grinding stone on grinding force and material removal in the rail grinding process

Abstract: The objective of this study is to explore the influence of grinding stone granularity on the grinding force and rail material removal behaviors using a rail grinding friction machine. The results indicate that with the increase in granularity, the grinding force, and friction coefficient in the grinding interface obviously increase, which brings about a rise in the hardness and grinding temperature-rise of rail specimens. The increase in the grinding stone granularity causes a fall in the grinding volume and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Therefore, under the same conditions, reducing the particle size of ZTA can increase the friction coefficient of the friction pair. This phenomenon is consistent with the results of Wang et al [62]. Figure 8(g) shows the surface roughness of the steel bars after grinded by seven Cu-ZTA cermets prepared in this paper.…”
Section: Grinding Behavior Of Cu-zta Cermetssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, under the same conditions, reducing the particle size of ZTA can increase the friction coefficient of the friction pair. This phenomenon is consistent with the results of Wang et al [62]. Figure 8(g) shows the surface roughness of the steel bars after grinded by seven Cu-ZTA cermets prepared in this paper.…”
Section: Grinding Behavior Of Cu-zta Cermetssupporting
confidence: 92%
“…Moreover, ZTA is not easy to peel because of its good bonding strength. When the particle size of ZTA is reduced, the abrasion loss of Cu-ZTA cermets on the steel bars increases, the reason is that the particle size of ZTA decreases and more ZTA is distributed at the grinding interface, so the abrasion loss on the steel bars increases [62]. used, the friction factor increases as the binder content increases because the binder can better coat the ZTA particles.…”
Section: Grinding Behavior Of Cu-zta Cermetsmentioning
confidence: 99%
“…Comparing the F10-4, F14-4 and F10-3, F14+16-1 specimens, it can be found that when the particle size of the ZTA particles reduced, the friction coefficient of the friction pair increased, because the low-diameter ZTA particles can be more uniformly dispersed in the matrix, the contact area of ZTA to the matrix can be increased during grinding process, so the friction coefficient increased. Theoretically, the friction coefficient of Fe-ZTA cermets produced after electroless nickel plating should be higher [25]. However, the comparison of F10-1, F10-3 and F10-2, F10-4 specimens did not give a similar trend.…”
Section: Grinding Test Of the Fe-zta Cermetmentioning
confidence: 86%
“…2 The rail grinding can remove and alleviate rail surface damages, thus improving the operation safety and the service life of rails. 3 Therefore, the rail grinding technique has become the most widely used method all over the world to maintain railway lines. 4,5 The rail grinding is in essence a vertical spindle surface grinding process between the end surface of grinding wheel (i.e.…”
Section: Introductionmentioning
confidence: 99%